2020
DOI: 10.1038/s41598-020-77836-y
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic droplet generation based on non-embedded co-flow-focusing using 3D printed nozzle

Abstract: Most commercial microfluidic droplet generators rely on the planar flow-focusing configuration implemented in polymer or glass chips. The planar geometry, however, suffers from many limitations and drawbacks, such as the need of specific coatings or the use of dedicated surfactants, depending on the fluids in play. On the contrary, and thanks to their axisymmetric geometry, glass capillary-based droplet generators are a priori not fluid-dependent. Nevertheless, they have never reached the market because their … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 49 publications
0
43
0
Order By: Relevance
“…It is worth mentioning that, since the DBALE method is firstly proposed here, the few examples are previous and recent works of the authors. In addition, in the work [10] we have found that ABALE method not only leads to large mesh distortion but is also very limited by (8). Last, the explicit surface description falls in the same category as ABALE method.…”
Section: Fluid Mechanicsmentioning
confidence: 93%
See 3 more Smart Citations
“…It is worth mentioning that, since the DBALE method is firstly proposed here, the few examples are previous and recent works of the authors. In addition, in the work [10] we have found that ABALE method not only leads to large mesh distortion but is also very limited by (8). Last, the explicit surface description falls in the same category as ABALE method.…”
Section: Fluid Mechanicsmentioning
confidence: 93%
“…5. Solution of ( 14) for the velocity field (15) using (a) BE (5b) or BL (3b) and (b) DBALE (6b), (10). Because of the symmetry, only the first quadrant has been plotted.…”
Section: Mesh Deformationmentioning
confidence: 99%
See 2 more Smart Citations
“…2013; Martínez-Calvo, Rubio-Rubio & Sevilla 2018) or by viscous stresses (Dewandre et al. 2020) have been extensively studied, and three distinct regimes can be identified by the flow rate provided by the nozzle: a periodic dripping regime for low flow rates, a dripping faucet regime for intermediate flow rates and a jetting regime for high flow rates. (ii) Ligaments stretched between two disks, mainly one of the disks being pulled up at a constant velocity or acceleration, have been studied by Zhang, Padgett & Basaran (1996), Vincent, Duchemin & Villermaux (2014 b ), Zhuang & Ju (2015), Wylie, Bradshaw-Hajek & Stokes (2016) and Brulin, Tropea & Roisman (2020).…”
Section: Introductionmentioning
confidence: 99%